Bimbingan Kelompok dengan Teknik Self-Management untuk Meningkatkan Manajemen Waktu Siswa - Setiawan, Andre; Antika, Eni Rindi; Hariyadi, Sigit (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2024)
Learning is an activity that requires effective time management to achieve productivity and efficiency. However, many students exhibit behaviors that do not reflect optimal time management. A preliminary study was conducted by distributing a time management scale to Grade X students of SMAN 14 Semarang. The results indicated that 10.3% of students had very low time management, 44.8% low, 31% high, and 13.7% very high. This research examines the impact of group counseling services using self-management to improve students' time management. The study employed a quantitative approach with an experimental method. Data analysis included descriptive and inferential statistical analyses using the Wilcoxon test. Descriptive analysis results showed an increase in the average time management score of the experimental group from 89.8 in the pre-test to 120.6 in the post-test, while the control group showed no improvement, with scores decreasing from 88.2 to 85.8. The Wilcoxon test for the experimental group yielded a Z Score of 2.023 with a significance level of 0.043 (< 0.05), indicating a significant improvement in students' time management. Conversely, the Wilcoxon test for the control group yielded a Z Score of 0.368 with a significance level of 0.713 (> 0.05), indicating no improvement. Based on these findings, it can be concluded that group counseling with the self-management technique effectively improves students' time management. This approach emphasizes the importance of students' self-control in modifying their behavior, significantly enhancing their time management skills.